Automated Shoe Metrology by X-Ray Computed Tomography - Leipert, Martin; Herl, Gabriel; Müller, Michael; Meskemper, Joshua; Zabler, Simon (3DBODY.TECH 2023 - 14th International Conference and Exhibition on 3D Body Scanning and Processing Technologies, 2023)

Integer Optimization of CT Trajectories using a Discrete Data Completeness Formulation - Schneider, Linda-Sophie; Herl, Gabriel; Maier, Andreas (CT Meeting 2024, 2024)
X-ray computed tomography (CT) plays a key role in digitizing three-dimensional structures for a wide range of medical and industrial applications. Traditional CT systems often rely on standard circular and helical scan trajectories, which may not be optimal for challenging scenarios involving large objects, complex structures, or resource constraints. In response to these challenges, we are exploring the potential of twin robotic CT systems, which offer the flexibility to acquire projections from arbitrary views around the object of interest. Ensuring complete and mathematically sound reconstructions becomes critical in such systems. In this work, we present an integer programming-based CT trajectory optimization method. Utilizing discrete data completeness conditions, we formulate an optimization problem to select an optimized set of projections. This approach enforces data completeness and considers absorption-based metrics for reliability evaluation. We compare our method with an equidistant circular CT trajectory and a greedy approach. While greedy already performs well in some cases, we provide a way to improve greedy-based projection selection using an integer optimization approach. Our approach improves CT trajectories and quantifies the optimality of the solution in terms of an optimality gap.<br

Reduktion von Metallartefakten durch multipositionale Datenfusion in der industriellen Röntgen-Computertomographie - Herl, Gabriel; Hiller, Jochen; Kasperl, Stefan; Maier, Andreas (Technisches Messen, 2019)
Zusammenfassung Metallartefakte stellen eine große Herausforderung für das Messen mit Röntgen-Computertomographie dar. Dieser Beitrag stellt die Methode der multipositionalen Datenfusion zur Reduktion von Metallartefakten vor. Dazu werden mehrere Scans desselben Objekts bei unterschiedlicher Objekt-positionierung durchgeführt, aufeinander registriert und zur Fusion gemeinsam unter Betrachtung eines lokalen Gütemaßes rekonstruiert. In praxisnahen Experimenten wird der Mehrwert der Methode gezeigt. Insbesondere wird dargestellt, wie mit wenig Aufwand und ohne Vorwissen Kunststoffstrukturen trotz starker Metallartefakte sichtbar gemacht werden können, womit das Verfahren ein Alleinstellungsmerkmal gegenüber den existierenden Metallartefaktreduktionsverfahren aufweist. Abstract Metal artifacts represent a major challenge for measuring with X-ray computed tomography. This paper presents a method for multipositional data fusion for the reduction of metal artifacts. For this purpose, several scans of the same object are performed with different object positioning, registered on each other and then reconstructed together using a local quality measure. The added value of the method is demonstrated in practical experiments. In particular, it is shown how plastic structures can be made visible despite strong metal artifacts with little effort and without prior knowledge, giving the method a unique selling point compared to existing metal artefact reduction methods.
Keywords: X-ray computed tomography; CT; metal artifact reduction; multipositional data fusion

Volumetric Instance Detection for Overlapping Shoes in Computed Tomography - Leipert, Martin; Herl, Gabriel; Zabler, Simon; Maier, Andreas (13th Conference on Industrial Computed Tomography, 2024)